Immunosuppression: What's Standard and What's New? - Witt, Chad A.; Hachem, Ramsey R. (Seminars in Respiratory and Critical Care Medicine, 2013)
Lung transplantation is the ultimate treatment option for patients with end-stage lung disease. Chronic rejection, in the form of bronchiolitis obliterans syndrome, and noncytomegalovirus infections are the major causes of morbidity and mortality beyond the first year after transplantation. Most lung transplant recipients are treated lifelong with a three-drug immunosuppression regimen consisting of a calcineurin inhibitor, an antimetabolite, and low-dose corticosteroids. However, induction and maintenance immunosuppression strategies vary widely between centers, and a consensus on the ideal management of this patient population remains elusive. Over the past 20 years, several studies comparing the calcineurin inhibitors cyclosporine and tacrolimus and other studies comparing the antimetabolites azathioprine and mycophenolate mofetil have been performed. Additionally, the role of mammalian target of rapamycin (mTOR) inhibitors in the treatment of lung transplant recipients and the utility of azithromycin to treat and prevent bronchiolitis obliterans syndrome are areas of active investigation. This review discusses induction and traditional maintenance immunosuppressive agents and regimens and the evidence that exists to help guide therapy. Newer research involving the use of mTOR inhibitors in place of calcineurin inhibitors or antimetabolites and azithromycin for the treatment and prevention of bronchiolitis obliterans syndrome is also explored.
Keywords: lung transplantation; induction immunosuppression; maintenance immunosuppression